Conexão alternativa do capacitor de saída em conversores integrados para drivers de LEDs e seu impacto na redução da ondulação de baixa frequência - Spode, Nelson da Silva (2023)
This thesis presents the conception, analysis, modeling, and experimental verification of a proposal for an alternative connection of the output capacitor in integrated converters aiming to reduce capacitances in LED drivers. Although advantageous in several aspects, the integration of converters leads to the loss of independence between converter stages, as both stages are controlled by the same active switch. This condition makes it impractical to adopt control techniques that directly act on the duty-cycle of the integrated switch to mitigate low-frequency ripple in the output current without distorting the input current. The low-frequency ripple transferred from the bus voltage to the LED current has been studied for integrated converters operating with a constant duty-cycle. To comply with the IEEE 1789-2015 recommendation, integrated converters use high capacitance values to mitigate low-frequency ripple. Converters operating in discontinuous conduction mode (DCM) have been widely adopted because they transfer less ripple to the output than converters operating in continuous conduction mode (CCM). A new circuit configuration for the integrated buck-boost power control stage with a buck-boost power factor correction stage is explored in this work as a technique to minimize low-frequency output ripple for converters operating with a constant duty-cycle. The proposed circuit provides current feedback to the bus capacitor, working to reduce the low-frequency ripple of the output current and the bus voltage. Dynamic models for the proposed converter in CCM and DCM are obtained and used to determine the output current modulation as a function of converter parameters. It is shown that the proposed topology in CCM results in lower low-frequency ripple than a conventional counterpart at the same operating point. A design example for a 95 W driver powering a 98.8 V / 960 mA LED load is presented, comparing the conventional integrated converter with the structure proposed in this thesis. Experimental results show that the proposed arrangement can achieve similar results to the conventional circuit in efficiency, THD, or semiconductor stress, while the obtained output current modulation, equal to 8,66 %, is 3.5 times lower than that of the conventional circuit at the same operating point and component values.